2022
DOI: 10.3389/fmicb.2022.960747
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pit latrine microbiota reveals depth-related variation in composition, and key parameters and taxa associated with latrine fill-up rate

Abstract: Pit latrines are used by billions of people globally, often in developing countries where they provide a low-tech and low-cost sanitation method. However, health and social problems can arise from a lack of emptying or maintenance of these facilities. A better understanding of the biological and environmental parameters within pit latrines could inform attempts to enhance material decomposition rates, and therefore slow fill-up rate. In this study, we have performed a spatial analysis of 35 Tanzanian pit latri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies have reported more variability of physical and chemical properties of pit latrines at the surface compared to deeper layers [39], a variability we did not observe in the microbial communities. Additionally, Ijaz et al [14] found changes in microbial communities with depth, with more gut-associated taxa at layers closer to the surface and more environmental-associated taxa with pit latrine depth. These differences may be due to taxa resolution, as this study is the first, to our knowledge, to report genus-level microbial community characteristics of lined pit latrines.…”
Section: Guidance For Public Health Sampling Of Pit Latrines and Hous...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported more variability of physical and chemical properties of pit latrines at the surface compared to deeper layers [39], a variability we did not observe in the microbial communities. Additionally, Ijaz et al [14] found changes in microbial communities with depth, with more gut-associated taxa at layers closer to the surface and more environmental-associated taxa with pit latrine depth. These differences may be due to taxa resolution, as this study is the first, to our knowledge, to report genus-level microbial community characteristics of lined pit latrines.…”
Section: Guidance For Public Health Sampling Of Pit Latrines and Hous...mentioning
confidence: 99%
“…However, molecular-based microbial studies for pit latrines are limited. Torondel et al [8] examined pit latrines in Vietnam and Tanzania; Byrne et al [6] reported the microbial communities in South African pour-flush toilets; Ijaz et al [14] compared unlined pit latrine microbial communities to latrine fill-up rates in Tanzania, and de los Reyes et al [15] compared the microbial communities in pour-flush toilets to that of a ventilated improved pit latrine (VIP) in South Africa. These first studies allowed insights on likely methanogenic and sulfate-reduction processes occurring in pit latrines, and the relationships between environmental conditions and degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…43 Scientific evidence about differences between blackwater that has been stored in containment in comparison to conventional wastewater sludges is mounting, including dewatering performance, 40,34,37,41,44 protein-like fractions of extracellular polymeric substances (EPS), 40,41 particle size distribution, 45,44 fibers and lipids, 46,47 rheological properties, 48,37 and microbial communities. 49 The assumption that waste streams have similar characteristics and properties has detrimental impacts on the design and operation of the conveyance and treatment. For example, dumping of stored wastewater in sewers can result in blockages due to higher than planned levels of inert solids.…”
Section: Wastewater Streams From Human Feces Are Not All the Same And...mentioning
confidence: 99%
“…A treatment plant may include stages of sludge treatment, including thickening, digestion, dewatering, and hygienization, depending on the type of wastewater treatment process and the destination of the sludge . Scientific evidence about differences between blackwater that has been stored in containment in comparison to conventional wastewater sludges is mounting, including dewatering performance, ,,,, protein-like fractions of extracellular polymeric substances (EPS), , particle size distribution, , fibers and lipids, , rheological properties, , and microbial communities …”
Section: Why Does Terminology Matter?mentioning
confidence: 99%